2005
DOI: 10.1126/science.1106305
|View full text |Cite
|
Sign up to set email alerts
|

Marine Fish Egg Hydration Is Aquaporin-Mediated

Abstract: The positive buoyancy of marine fish eggs in sea water, allowed by hydration of the oocyte, is critical for their survival and dispersion in the ocean. We isolated an aquaporin, SaAQP1o, that belongs to a unique subfamily of aquaporin-1—like channels specifically evolved in teleosts and mainly expressed in the ovary. We further show that hormone-induced fish oocyte hydration is a highly controlled process based on the interplay between protein hydrolysis and the translocation of SaAQP1o to the plasma membrane,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
128
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(138 citation statements)
references
References 4 publications
7
128
3
Order By: Relevance
“…In Japanese medaka, aqp1a was most abundant in the intestine, spleen and kidney but also present at lower levels in all other tissues examined, which in part may reflect its general expression in erythrocytes and endothelial barriers . This ubiquitous tissue distribution is in accordance with zebrafish, sea bream, Atlantic salmon and European eel, and marine medaka (Fabra et al, 2005;Martinez et al, 2005;TingaudSequeira et al, 2010;Tipsmark et al, 2010b;Kim et al, 2014). The role of Aqp1a in osmoregulatory tissues is most likely linked to transepithelial water transport, whereas its physiological role in other tissues is unknown.…”
Section: Tissue Distribution Of Aquaporins and Nkcc2mentioning
confidence: 77%
“…In Japanese medaka, aqp1a was most abundant in the intestine, spleen and kidney but also present at lower levels in all other tissues examined, which in part may reflect its general expression in erythrocytes and endothelial barriers . This ubiquitous tissue distribution is in accordance with zebrafish, sea bream, Atlantic salmon and European eel, and marine medaka (Fabra et al, 2005;Martinez et al, 2005;TingaudSequeira et al, 2010;Tipsmark et al, 2010b;Kim et al, 2014). The role of Aqp1a in osmoregulatory tissues is most likely linked to transepithelial water transport, whereas its physiological role in other tissues is unknown.…”
Section: Tissue Distribution Of Aquaporins and Nkcc2mentioning
confidence: 77%
“…The mechanisms of rainbow trout oocyte hydration thus remain unknown and require specific investigations. In the marine teleost, seabream (Sparus aurata) it was recently shown that oocyte hydration is aquaporin mediated (Fabra et al, 2005). Therefore, it is possible that a similar membrane-mediated mechanism also occurs in rainbow trout.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, specific knockdown of AaAQP2 through RNAi, although significantly decreasing the corresponding transcript levels, did not give any noticeable phenotype (Drake et al, 2010). In teleosts, a functional AQP1-related water channel has been described in oocytes where it plays a role during oocyte hydration prior to ovulation (Fabra et al, 2005;Zapater et al, 2011). During vitellogenesis, basal oocytes of B. germanica increase in size exponentially as a result of the incorporation of yolk precursors and water (Belles et al, 1987;Ciudad et al, 2006;Martín et al, 1995), and AQPs may be involved in oocyte water balance during this process.…”
Section: A Herraiz and Othersmentioning
confidence: 99%